Pelatihan Pembuatan Video Dokumenter di Desa Bandung Kecamatan Banjar Kabupaten Pandeglang Banten Indonesia - Lathiful Anwar; Azzahra Nurulhaqqni Ramadhani; Abdullah Noerkholis; Puspa Dewi Amanda; Agus Sukirno (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Documentaries have traditionally served as a means to effectively communicate complex concepts and information in a concise and more accessible manner. Documentary films have a dual purpose: to provide information about factual events and also function as a means to advertise products or brands. This outreach activity focuses on increasing the capacity and abilities of MSME actors in Bandung Village, Banjar District, Pandeglang Regency, Banten. The goal is to help them effectively use technology to create engaging documentaries that can increase sales and marketing efforts through online platforms. Furthermore, the capabilities and expertise of MSME actors in Bandung Village, Banjar District, Pandeglang Regency, Banten, cover the entire production process, including pre-production, production and post-production.